PENGARUH BOOK-VALUE (BV), EARNING PER SHARE (EPS) DAN DEBT EQUIITY RATIO (DER) TERHADAP HARGA SAHAM: STUDI KASUS DENGAN DATA PANEL DI INDONESIA - Singgih Santoso (Fakultas Bisnis UKDW, 2009)
This article develop a regression based model in which stock price, as a dependent vmiable, be inJluenced with some independent voriabels, such as book value @y), earning per share @PS) and debt equity ratio @ER). Model was built based ontwenty-six companies'financial statement data listed on Indonesio Stock Exchanges, particularly in industrial sector, ouer period 2003-200d. Testing with m,any theoretical methods shows that the best model is cross-section specific component with fixed effect model.